Indoor Mobile Robot Platform (IMRP) Phase III design and implementation of a microcontroller-based mobile robot with modular sensor and motor blocks, digital speed control and remote access using a wireless router - Dungca, Frank Theodore A. (2006)
The Indoor Mobile Robot Platform Phase III (IMRP III) features expandability and remote access capability by implementing a modular design for the functional blocks and using a wireless router for remote communication. Two Z8Encore microcontrollers are used to control the functional blocks of the mobot; one microcontroller is connected to the sensor modules and another microcontroller is used for motor control. Data from the environment is acquired using ultrasonic sensors and proximity sensors. These sensors are placed at different levels to accurately gather information. The motor module has a closed-loop digital speed control that allows correction and movement control. Communication through a wireless router allows the user to know the current status of the sensors of the mobot and issue movements to the mobot even without an onboard personal computer through the eZ80Acclaim Microcontroller Unit (MCU) designed as a Java Applet. The eZ80Acclaim MCU is interfaced with the two Z8Encore microcontrollers using Universal Asynchronous Receiver Transmitter (UART). The implementation of the IMRP III results in a robust mobot platform suited for localization and mapping.